A Novel Microbiosensor Microarray for Continuous ex Vivo Monitoring of Gamma-Aminobutyric Acid in Real-Time - Hossain, Imran; Tan, Chao; Doughty, Phillip T.; Dutta, Gaurab; Murray, Teresa A.; Siddiqui, Shabnam; Iasemidis, Leonidas; Arumugam, Prabhu U. (Frontiers in Neuroscience, 2018)
Gamma-aminobutyric acid (GABA) is a major inhibitory neurotransmitter that is essential for normal brain function. It is involved in multiple neuronal activities, including plasticity, information processing and network synchronization. Abnormal GABA levels result to severe brain disorders and therefore GABA has been the target of a wide range of drug therapeutics. GABA being non-electroactive is challenging to detect in real time. To date, GABA is detected mainly via microdialysis with a high-performance liquid chromatography system that employs electrochemical and spectroscopic methodology. However, these systems are bulky and unsuitable for real-time continuous monitoring. As opposed to microdialysis, biosensors are easy to miniaturize and are highly suitable for in vivo studies; they selectively oxidize GABA into a secondary electroactive product (usually hydrogen peroxide, H2O2) in the presence of enzymes, which is then detected by amperometry. Unfortunately, this method requires a rather cumbersome process with prereactors and relies on externally applied reagents. Here, we report the design and implementation of a GABA microarray probe that operates on a newly conceived principle. It consists of two microbiosensors, one for Glutamate (Glu) and one for GABA detection, modified with glutamate oxidase and GABASE enzymes respectively. By simultaneously measuring and subtracting the H2O2 oxidation currents generated from these microbiosensors, GABA can be detected continuously in real time and without the addition of any externally applied reagents. The detection of GABA by this probe is based upon the in-situ generation of α-ketoglutarate from the Glu oxidation that takes place at the Glu microbiosensor. A GABA sensitivity of 36±7% pA μM-1 cm-2, which is 26-fold higher than reported in the literature, and a Limit of Detection of 2±6% µM were achieved in in vitro setting. These results indicate that the developed GABA probe constitutes a novel and powerful neuroscientific tool that could be employed in the future for in vivo longitudinal studies of the combined role of GABA and Glu (a major excitatory neurotransmitter) signaling in brain disorders, such as epilepsy and Traumatic Brain Injury (TBI), as well as in preclinical trials of potential therapeutic agents for the treatment of these disorders